2011
DOI: 10.1038/nature09786
|View full text |Cite
|
Sign up to set email alerts
|

The unusual minimum of sunspot cycle 23 caused by meridional plasma flow variations

Abstract: Direct observations over the past four centuries show that the number of sunspots observed on the Sun's surface varies periodically, going through successive maxima and minima. Following sunspot cycle 23, the Sun went into a prolonged minimum characterized by a very weak polar magnetic field and an unusually large number of days without sunspots. Sunspots are strongly magnetized regions generated by a dynamo mechanism that recreates the solar polar field mediated through plasma flows. Here we report results fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 27 publications
8
109
3
1
Order By: Relevance
“…The rotation rate of sunspots varies with area and age (Ward 1966;Howard et al 1984;Zappalá & Zuccarello 1991), which has been suggested to be due to the different anchor depths of different types of sunspots (Nesme-Ribes et al 1993;Rhodes et al 1990). Moreover, the differential rotation of all tracers of rotation is also affected by large-and small-scale flows, such as torsional oscillations (Covas et al 2001;Howe et al 2009;Antia & Basu 2010), meridional flows (Javaraiah & Ulrich 2006;Javaraiah 2010;Nandy et al 2011), supergranules (Beck & Schou 2000), etc. Therefore, shortening the fit period reveals the detailed variation of rotation at short time scales, yielding more accurate momentary rotation rates, stronger non-axisymmetries and and a higher accuracy when finding ALs.…”
Section: Discussionmentioning
confidence: 99%
“…The rotation rate of sunspots varies with area and age (Ward 1966;Howard et al 1984;Zappalá & Zuccarello 1991), which has been suggested to be due to the different anchor depths of different types of sunspots (Nesme-Ribes et al 1993;Rhodes et al 1990). Moreover, the differential rotation of all tracers of rotation is also affected by large-and small-scale flows, such as torsional oscillations (Covas et al 2001;Howe et al 2009;Antia & Basu 2010), meridional flows (Javaraiah & Ulrich 2006;Javaraiah 2010;Nandy et al 2011), supergranules (Beck & Schou 2000), etc. Therefore, shortening the fit period reveals the detailed variation of rotation at short time scales, yielding more accurate momentary rotation rates, stronger non-axisymmetries and and a higher accuracy when finding ALs.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 17 shows that the plumes of decayed active-region flux moving poleward have been of more mixed polarity since the cycle 23 polar reversal than before. One explanation is that the meridional flows are so fast that the leading polarities in the two hemispheres do not have time to interconnect and interact with each other before being swept poleward (e.g., Schrijver and Liu, 2008;Wang et al, 2009;Nandy et al, 2011;Jiang et al, 2013). An alternative explanation is that the active region Joy's law tilts changed their hemispheric bias during cycle 23 (e.g., Jiang et al, 2013;Petrie, 2012).…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 99%
“…Variation of the flow during the Transition are noteworthy: during solar cycle 23 the meridional flow extended up to the poles while in cycle 22 the circulation had switched equatorward near latitude 60 • (Dikpati et al 2010).The authors suggested that this may have been at the origin of the longer duration of cycle 23. Nandy et al (2011) introduced a fast meridional flow in the first half of the solar polar cycle followed by a slower flow in the second half. It appears that this introduction is able to reproduce the main characteristics of the sunspot cycle 23.…”
Section: Origin Of Pulsationsmentioning
confidence: 99%
“…We refer to papers and reviews by Russell et al (2010), Lockwood et al (2010), Lockwood (2012), Nandy et al (2011), Solanki and Krivova (2011), de Jager andDuhau (2011), de Jager (2012). Quoting Russell et al (2010): "Previous solar minima had occurred in 1996, 1986, 1976 and 1966, so Uncertainty remained at that time, as appears from a quotation by Weiss (2010): Is this just an abnormal fluctuation or are we about to experience a Maunder-like Grand Minimum?…”
Section: Introductionmentioning
confidence: 99%